USAHA OPTIMALISASI PAJAK HIBURAN WARUNG INTERNET DAN SUMBANGANNYA TERHADAP PENDAPATAN ASLI DAERAH KOTA PEKANBARU TAHUN 2014-2016 - Vera Melly Yanti; Erman M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Regional Regulation No. 5 of 2011 on the Entertainment Tax is a The government policy to establish rules for online shop owners. Due to the existence of this regional regulation, the initial regional income of Pekanbaru can reach the target set by the government. To find out about the Pekanbaru city government's policy regarding Pekanbaru's regional regulation, the researchers wanted to know about efforts to optimize the taxes on entertainment in Internet cafes and their contributions to the city's initial income. Pekanbaru in 2014-2016. This study aims to (1) describe the efforts to optimize the taxes on entertainment in Internet cafes and their contributions to the initial income of the city of Pekanbaru for the period 2014-2016, (2) to discover the factors that influence the efforts to optimize taxes on Internet entertainment in the cafeteria in Pekanbaru and their contributions to the original income in the year 2014-2016 Pekanbaru. This research took place in the city of Pekanbaru. Data collection techniques are performed by interview and documentation. While the data analysis technique is performed by qualitative data analysis. The results of the study concluded that efforts to optimize Internet cafe entertainment taxes and their contributions to Pekanbaru's original income in 2014-2016 did not work optimally. The inhibiting factor is the lack of awareness of the responsibilities of online store owners, which hinders the achievement of goals each year. Lack of government oversight of Internet store owners, so unlicensed cybercafes can still operate without paying taxes.Keywords: optimization, tax on entertainment, donations.